2020
DOI: 10.1177/2045894020933087
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension with adult respiratory distress syndrome: prevalence, clinical impact, and association with central venous pressure

Abstract: Pulmonary hypertension (PH) occurs in patients with acute respiratory distress syndrome (ARDS); the most severe form comprises acute cor pulmonale (ACP). Here, we investigated the prevalence of PH in patients with ARDS to evaluate its correlation with ACP risk, ARDS severity and central venous pressure (CVP). We conducted a secondary analysis using data from the MIMIC-III open-source clinical database. The prevalence of PH associated with new-onset ARDS during the first 72 h after intensive care unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Although RV dysfunction has been described in patients with acute respiratory distress syndrome (ARDS), the prevalence of RV dysfunction in our study is higher than what has been reported in non-COVID-19 patients with ARDS. [27][28][29] It is possible that RV dysfunction associated with COVID-19 may be pathologically distinct for several reasons. First, macroand microvascular thrombosis from deranged coagulation pathways could induce RV dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Although RV dysfunction has been described in patients with acute respiratory distress syndrome (ARDS), the prevalence of RV dysfunction in our study is higher than what has been reported in non-COVID-19 patients with ARDS. [27][28][29] It is possible that RV dysfunction associated with COVID-19 may be pathologically distinct for several reasons. First, macroand microvascular thrombosis from deranged coagulation pathways could induce RV dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Splitting patients into a derivation and validation cohort, they identified four variables: pneumonia as a cause of ARDS, driving pressure ≥ 18 cm H 2 O, arterial oxygen partial pressure to fractional inspired oxygen (PaO 2 /FiO 2 ) ratio < 150 mmHg and arterial carbon dioxide partial pressure ≥ 48 mmHg, which comprised the ACP risk score. The ACP risk score was subsequently validated by Li et al [ 17 ] in a retrospective analysis of 2434 patients. Additionally, the ACP score correlated with an increased incidence of pulmonary hypertension in patients with ARDS, with each increase in ACP score associated with an increase in the prevalence of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated mean CVP (>12 mmHg) is independently associated with the occurrence of PH in patients with ARDS, thus highlighting the importance of CVP monitoring in the management of ARDS. 77 , 78 …”
Section: Discussionmentioning
confidence: 99%
“…Elevated mean CVP (>12 mmHg) is independently associated with the occurrence of PH in patients with ARDS, thus highlighting the importance of CVP monitoring in the management of ARDS. 77,78 Therefore, the long-term follow-up of cardiopulmonary function for COVID-19 survivors could become a relevant health problem in the near future, given the large number of patients infected by COVID-2019 worldwide. In this context, measuring the venous congestion in a quick and practical manner by the new VenCoM device, could be extremely useful for both the management of clinical PH following COVID-19 during the acute phase, and the monitoring of pulmonary and vascular remodeling effects after recovery to provide the best long-term management of survivors.…”
Section: Vencom In Pandemic Covid-19mentioning
confidence: 99%